FROM DARKNESS TO LIGHT, OR THE EMERGENCE OF RELIGIOUS CONTROL IN CENTRAL ASIA AND KAZAKHSTAN (Proceedings of International Educators Conference, 2023)
This article talks about the establishment of the religious control of Central Asia and Kazakhstan, its internal and external activities in the 1940s - 1950s.